Satisfaction With Dwelling Unit Attributes and Infrastructure Within Selected Public Housing Estates in Northern Nigeria - Maina, Joy; Dagoli, Musa; Abdulkadir, Abdulrazak; Muhammad, Nurudeen; Muhammed, Isa; Yusuf, Bukhari; Mtan, Ternenge; Abdulrazaq, Mahmud (Universitas Indonesia, 2021)
This study assessed satisfaction with dwelling unit attributes as well as support services and infrastructure within public housing estates across Northern Nigeria as such studies are rare in literature but important for design and policymaking. Results of descriptive statistics, Principal Component Analyses and Regression from 125 respondents in Abuja, Dutse, Sokoto, Gombe and Potiskum revealed that support services and infrastructure notably water supply and waste disposal were inadequate. Although residents were fairly satisfied with their dwelling units (M 3.13), water supply influenced satisfaction ratings for service-related spaces including baths, toilets, cooking and storage. Other areas of dissatisfaction were number of bedrooms, quality of construction and sizes of living spaces. Residents were most satisfied with quality of natural lighting, ventilation, location of houses, noise as well as privacy levels. Results from PCA revealed that residents view satisfaction with their dwelling unit attributes and infrastructure in terms of design and cost, services and indoor environmental quality as well as electricity supply and noise levels. These three factors emerged as significant predictors of satisfaction with dwelling unit attributes and infrastructure, F (20.54, 18), p=0.000, R2=0.777, in a model that included tenant characteristics. Findings imply that inadequacy in water supply requires urgent attention within public housing estates in the region. Importantly, user perception in terms of the three predictors of satisfaction ought to guide design of future dwelling units within public housing estates in Northern Nigeria.